A Halogen Bonding 1, 3‐Disubstituted Ferrocene Receptor for Recognition and Redox Sensing of Azide. Issue 2 (29th August 2016) - Lim, Jason Y. C.; Beer, Paul D.
Abstract : A neutral redox‐active acyclic halogen bonding (XB) receptor with a ferrocene core functionalised at the 1, 3‐positions of a cyclopentadienyl ring with iodotriazole motifs is prepared. Owing to favourable host‐guest size‐complementarity, the receptor was found to be selective for azide over a diverse range of anions with different geometries. Voltammetric studies revealed the unique ability of the XB ferrocene receptor to selectively sense azide via a significant cathodic shift of its ferrocene/ferrocenium redox couple. Notably, much weaker binding of azide was observed for the hydrogen bonding 1, 3‐bis‐prototriazole ferrocene receptor analogue, which also displayed a poorer electrochemical response, suggesting that halogen bonding interactions play crucial roles in the binding and sensing of azide. Abstract : The first halogen bonding redox‐active ferrocene receptor that binds and electrochemically senses azide selectively in solution is reported, which shows greatly improved sensitivity and discrimination compared to its hydrogen bonding analogue.